Robbins & cotran pathologic basis of disease. Volume I - Kumar, Vinay, 1944-; Abbas, Abul K.; Aster, Jon C.; Turner, Jerrold R.; James A. Perkins; Sibgh, Monoj K. (Elsevier; RELX India, 1974)
"Readable and highly illustrated 'Robbins and Cotran Pathologic Basis of Disease' 10th Edition presents an in-depth state-of-the-art overview of human diseases and their cellular and molecular basis. This best-selling text delivers the latest most essential pathology knowledge in a readable interesting manner ensuring optimal understanding of the latest basic science and clinical content. More than 1 000 high-quality photographs and full-color illustrations highlight new information in molecular biology disease classifications new drugs and drug therapies and much more. . Key Features - Provides uniquely authoritative and readable coverage, ideal for USMLE or specialty board preparation, as well as for coursework. - Covers the hot topics you need to know about, including novel therapies for hepatitis C, classification of lymphomas, unfolded protein response, non-apoptotic pathways of cell death, coronavirus infections, liquid biopsy for cancer detection, regulation of iron absorption, clonal hematopoiesis and atherosclerosis, thrombotic microangiopathies, heparin-induced thrombocytopenias, inflammatory myopathies, genetic tools for treatment of cystic fibrosis, and many more. - Uses an outstanding full-color, user-friendly design to simplify your study and quickly direct you to the information you need to know, with learning features such as boldface overviews at the beginning of each section, key concepts boxes, suggested readings, schematic diagrams that illustrate complex concepts, and new gross and microscopic figures for clarity of morphology. - Brings you up to date with the latest information in molecular and genetic testing, mechanisms of disease, personalized medicine and its impact on treatment of human diseases, the role of microbiome and metabolome in non-communicable diseases, and much more. - Provides access to a wealth of interactive ancillaries online: pathology case studies, videos, self-assessment questions, Targeted Therapy boxes that discuss drug therapy for specific diseases, interactive cases, and more." -- back cover.